PENINGKATAN HASIL BELAJAR IPA SISWA MELALUI MODEL PEMBELAJARAN CTL (CONTEXTUAL THEACING AND LEARNING) DI KELAS V A SDN 021 TANJUNG PALAS - Jenny ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low result belaja fifth grade science students at SDN 021 Tanjung Palas, out of 25 students only 8 students (32.00%), rendahnnya learning outcomes is caused by: (a) students lack enthusiasm in learning; (b) students are not able to answer questions that are of reason; (c) teachers do not involve students actively in learning; (d) less than the maximum in using props; and (e) the level of students' understanding of the subject matter IPA is still low. This research is a classroom action research (PTK), this study aims to describe the results of learning through the use of learning model CTL. The subjects were students of class V A 021 SDN Tanjung Palas. This study was conducted by two cycles. Improved learning outcomes in terms of four categories, namely absorption, the effectiveness of learning, mastery learning completeness students both individual and classical completeness and thoroughness of learning outcomes. The instrument used for data collection is an oral test and a written test in the form of worksheets that do after the learning process. The results showed that the learning outcomes of science students has increased at each cycle, as shown by the acquisition of mastery learning students, the first cycle the number of students who pass are 15 students or 60% and the second cycle the number of students who pass are 22 students or 88% , It can be concluded that through CTL learning model can improve learning outcomes a fifth grade science students at SDN 021 Tanjung Palas.